Fixed Solar Eruption: A Case Report - Yukiko Tateno; Michie Katsuta; Akihiko Asahina; Yoshimasa Nobeyama (JEADV Clinical Practice, 2026)
ABSTRACT Fixed eruption is characterized by recurrent lesions at identical anatomical sites after exposure to a trigger. Although most cases are drug‐induced, ultraviolet (UV) radiation has also been reported as a causative factor. We report a case of fixed solar eruption diagnosed by histopathology and 308 nm excimer light phototesting. A 30‐year‐old Japanese man presented with recurrent erythema localized to hyperpigmented macules on both forearms following sunlight exposure. 308 nm excimer light phototesting induced erythema in hyperpigmented macules. Histopathology revealed pigmentary incontinence and basal CD8‐positive lymphocytes in hyperpigmented macules. The lesions were controlled with photoprotection alone. Despite the absence of UVA‐based evaluation, the clinical course, phototesting results and histopathological findings supported the diagnosis of fixed solar eruption. Fixed solar eruption can be effectively controlled with appropriate photoprotection, highlighting the importance of prompt diagnosis.